Study of Lipid Profiles levels in Iraqi children with GH Deficiency Before and after 6 Months GH Replacement Therapy - Mithal R Alkubaisi1 , Hameed Hussein Ali2 , Fakhri J. Al-Dalla Ali1 , Abbas M. Rahmah3 (Indian Journal of Forensic Medicine & Toxicology, 2020)
This present study aimed to quantify serum lipid levels [Total cholesterol (TC), Triglyceride (TG), LowDensity Lipoprotein –cholesterol (LDL-c), Very Low Density Lipoprotein –cholesterol( VLDL-c), HighDensity Lipoprotein–cholesterol (HDL–c) ] quantified before and after 6 months of treatment in Iraqichildren with HGH deficiencyThis study was conducted at the National Center for Diabetes Treatment and Research of the MustansiriyaUniversity in Baghdad and for the period from, (October 2016 to July 2017). The study included 200 samplesdivided into two groups. The patient group included 100 children with short stature including 52 males and48 females with their age ranged from 5 to 12 years . For comparison, 100 samples (50 females and 50males) of healthy children corresponding to patients with sex, age were selected as control group.The results of the study showed Serum (TC), (TG), (LDL-C) and (VLDL) levels had a highly significantlyincreased in children GHD group when compared with controls group (P<0.001).Regarding serum (HDL-C) levels there was a highly significantly decreased in children GHD group whencompared with healthy children (P<0.001) before treatment, and after 6 months of treatment a decrease infat levels was observed in patients [ (TC), (TG) and (LDL-C), (VLDL), very significantly (p <0.001), whiletheir HDL-C level was higher than before treatment .To distinguish between GHD patients and the control group, the Receiver Operator Curve (ROC) analysisshowed a descending order of significance for the indicators that showed significant differences beforetreatment. The serum level of LDL-C was 0.77, followed by (TG) (0.637 ) ,(VLDL-C) (0.637),( TC) (0.626),and ( HDL-C) (0.614) respectively [this means that all variables managed to occupy a significant region ofROCIt was concluded from this study that there was a significant increase (P <0.001) in serum TG, TC, LDL-Cand VLDL-C, while the level of HDL-C in the blood decreased significantly in GHD children comparedwith healthy children. After 6 months of treatment rhGH has improved the lipid profile of children withgrowth hormone deficiency.